Reasons for not receiving the HPV vaccine among eligible adults: Lack of knowledge and of provider recommendations contribute more than safety and insurance concerns. (1st June 2020) - Fokom Domgue, Joël; Cunningham, Sonia A.; Yu, Robert K.; Shete, Sanjay
Abstract: Background: The upward trends of vaccine exemptions in Texas are alarming. While HPV vaccine rates in this State are among the lowest nationwide, factors that contribute to the low HPV vaccination uptake among adults remain unknown. In this study, we examined the main reasons for not receiving HPV vaccination among age‐eligible adults. Methods: The Texas health screening survey (2018), a multistage area probability design‐based survey of a representative sample of Texas residents, was used to identify 907 eligible adults (age ≥ 18 years) respondents, including 724 women aged ≤ 26 years in 2007 (≤38 years in 2018), and 183 men aged ≤ 21 years in 2011 (≤28 years in 2018). Participants who reported having never received an HPV shot, where asked the main reason for not receiving the vaccine. Results: Overall, 58.5% (95%CI: 55.1‐62.0) of vaccine eligible adults reported having never received the HPV vaccine. The most commonly reported reasons for not receiving it were: did not know about the vaccine (18.5% (14.9‐22.1)), and provider did not recommend (14.1% (10.9‐17.4)). In contrast, commonly perceived reasons such as: safety concerns (7.2% (4.8‐9.5)), lack of insurance (3.4% (1.7‐5.1), and concerns about increasing sexual activity if vaccinated (0.2% (0.0‐0.5)), were less frequently reported. Conclusion: Among vaccine‐eligible adults, safety and sexuality concerns do not appear to be the prime factors underlying low HPV vaccination rates. Rather than emphasizing them, educational interventions should aim at improving vaccine's knowledge, and enhancing provider recommendations on the necessity of HPV vaccination. Abstract : Among HPV‐vaccine eligible adults, lack of knowledge about the vaccine and lack of provider recommendations are the most commonly reported reasons for not receiving the HPV vaccine. In this population, educational interventions should focus on enhancing HPV vaccine's knowledge and provider recommendations of the necessity and awareness of HPV vaccination.